Combining 10% propolis with carbonated hydroxyapatite to observe the RANKL expression in a rabbit’s alveolar bone - Nungky Devitaningtyas; Ahmad Syaify; Dahlia Herawati (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Periodontitis causes an increased receptor activator level in the nuclear factor-κβ ligand (RANKL), which is one of the inflammatory mediators that plays a role in osteoclastogenesis. The open flap debridement (OFD) technique is the preferred treatment when accompanied by regenerative periodontal treatment using guided tissue regeneration (GTR) and guided bone regeneration (GBR). Carbonated hydroxyapatite is a GBR material that serves as a scaffold and has strong osteoconductive properties for bone regeneration. Propolis is natural product that can decrease osteoclastogenesis in periodontitis by decreasing the RANKL expression. Purpose: To investigate the RANKL expression after open flap debridement by applying carbonated hydroxyapatite to 10% propolis in the alveolar bone of rabbits. Methods: Nine induced-periodontitis rabbits (Oryctolagus cuniculus) were divided into three treatment groups of Group A OFD, Group B OFD followed by the application of carbonated hydroxyapatite, and Group C OFD followed by application of 10% propolis-carbonated hydroxyapatite. Each group was selected one to euthanised on the seventh, 14th and 28th day, respectively, and prepared using histology slides. The data was analysed using a two-way ANOVA followed by a post-hoc LSD test (p<0.05). Results: The RANKL expression in each group showed significant differences (p=0.00; p<0.05) on the seventh, 14th and 28th day. The post-hoc LSD test showed that the RANKL expression in the treatment group with carbonated hydroxyapatite-10% propolis had significant differences (p<0.05) in the intergroup analysis at different time points. Conclusion: Combining 10% propolis with carbonated hydroxyapatite in OFD treatment can decrease the RANKL expression in a rabbit’s alveolar bone.